Electoral politics influence expansion and titling of informal urban settlements - Beth Tellman; Meha Jain; Hallie Eakin; Dylan Connor; Felipe de Alba (Proceedings of the National Academy of Sciences, 2026)
Understanding what and who shapes urban growth and how it unfolds in the Global South is critical to ensure theories and predictive models of urban expansion and, consequently, global environmental change, are salient to contemporary contexts. Much of the urban expansion in the Global South occurs in informal settlements where urbanization is not officially permitted and residents often lack access to basic services and infrastructure. As a result, formalizing settlements becomes an asset for political transactions where politicians provide titles and improve conditions in exchange for residents’ votes. Yet the cumulative effect of these political transactions on land change remains unknown, rendering electoral dynamics absent from land system science models of urbanization. Here we use panel regression to examine the influence of electoral cycles and voting patterns on urban expansion and formalization of property titles from 1997–2015 in Mexico City. We find the distribution of land titles to residents increases in the months leading up to local elections, and more titles are given to core voting neighborhoods of the historically dominant party. Furthermore, urban built-up area increases in districts with higher electoral competition. These results demonstrate that electoral politics influence when and where the legal city boundary expands, who can access secure tenure, and potentially which settlements grow. These results imply sociopolitical dynamics shape urban sustainability. Incorporating quantified links between political dynamics and urban expansion could improve models of future urban growth and identify relevant levers to improve urban sustainability.